Burnout vermeiden (Assemble You, 2022)
Welcome to our Assemble You Learning Podcast According to a 2021 survey conducted by Indeed, more than half of employees suffer from burnout. In 2019, the World Health Organization (WHO) officially recognized that burnout is related to stress at work. Burnout is characterized by symptoms such as emotional exhaustion, cynicism and ineffectiveness, and is associated with mental and physical health problems such as an increased risk of cardiovascular disease, depression and anxiety. In this module, we aim to bring a better understanding of burnout and offer actionable tips to help alleviate burnout. Learning Objectives Learn what burnout is and what it means. Learn actionable techniques to limit or even prevent the negative effects of burnout.